Immunotherapy and lung cancer: from therapeutic cancer vaccination to novel approaches - Mazza, Valentina; Cappuzzo, Federico (Journal of Thoracic Disease, 2016)
In the last years, knowledge about immune system and cancer rapidly increased, becoming evident that immune system, when properly stimulated, can eradicate cancer cells (1,2). Immunotherapy includes two main approaches: passive and active immunotherapy. Passive immunotherapy consists in administering monoclonal antibodies targeting specific tumor-associated antigens (i.e., rituximab in lymphoma or trastuzumab in breast cancer). In lung cancer such strategy showed modest or no benefit with no agent so far approved for treatment of advanced disease. In 2009 cetuximab was not approved for first line treatment of advanced non-small cell lung cancer (NSCLC) despite the survival benefits showed by the combination of cetuximab plus chemotherapy in patients with EGFR mutation (3). Trials of trastuzumab or other HER2-targeted agents failed to demonstrate clinical benefit in NSCLC as monotherapy or combined with chemotherapy (4). Active immunotherapy includes therapeutic cancer vaccination (antigen specific immunotherapy), which aims to enhance T-cells response against specifically expressed tumor antigens, and immune check point inhibitors (non-antigen specific immunotherapies) which aim to “remove the brakes” on T-cells and restore the immune response against tumor cells (1,2,5).